Disparities in Cancer Care and the Asian American Population. (20th March 2021) - Lee, Richard J.; Madan, Ravi A.; Kim, Jayoung; Posadas, Edwin M.; Yu, Evan Y.
Abstract : : Asian Americans are the only racial/ethnic group in the U.S. for whom cancer is the leading cause of death in men and women, unlike heart disease for all other groups. Asian Americans face a confluence of cancer risks, with high rates of cancers endemic to their countries of origin due to infectious and cultural reasons, as well as increasing rates of "Western" cancers that are due in part to assimilation to the American diet and lifestyle. Despite the clear mortality risk, Asian Americans are screened for cancers at lower rates than the majority of Americans. Solutions to eliminate the disparity in cancer care are complicated by language and cultural concerns of this very heterogeneous group. This review addresses the disparities in cancer screening, the historical causes, the potential contribution of racism, the importance of cultural perceptions of health care, and potential strategies to address a very complicated problem. Noting that the health care disparities faced by Asian Americans may be less conspicuous than the structural racism that has inflicted significant damage to the health of Black Americans over more than four centuries, this review is meant to raise awareness and to compel the medical establishment to recognize the urgent need to eliminate health disparities for all. Implications for Practice: Cancer is the leading cause of death in Asian Americans, who face cancers endemic to their native countries, perhaps because of infectious and cultural factors, as well as those faced by all Americans, perhaps because of "Westernization" in terms of diet and lifestyle. Despite the mortality rates, Asian Americans have less cancer screening than other Americans. This review highlights the need to educate Asian Americans to improve cancer literacy and health care providers to understand the important cancer risks of the fastest-growing racial/ethnic group in the U.S. Eliminating disparities is critical to achieving an equitable society for all Americans. Abstract : Solutions are needed to eliminate disparities in cancer care for Asian Americans. This review addresses disparities in cancer screening, historical causes, the potential contribution of racism, the importance of cultural perceptions, and potential strategies to address this complicated problem.